Effect of an expansion in private sector provision of contraceptive supplies on horizontal inequity in modern contraceptive use: evidence from Africa and Asia - Do Mai; Godha Deepali; Hotchkiss David R (BMC, 2011)
Abstract Background One strategic approach available to policy makers to improve the availability of reproductive and child health care supplies and services as well as the sustainability of programs is to expand the role of the private sector in providing these services. However, critics of this approach argue that increased reliance on the private sector will not serve the needs of the poor, and could lead to increases in socio-economic disparities in the use of health care services. The purpose of this study is to investigate whether the expansion of the role of private providers in the provision of modern contraceptive supplies is associated with increased horizontal inequity in modern contraceptive use. Methods The study is based on multiple rounds of Demographic and Health Survey data from four selected countries (Nigeria, Uganda, Bangladesh, and Indonesia) in which there was an increase in the private sector supply of contraceptives. The methodology involves estimating concentration indices to assess the degree of inequality and inequity in contraceptive use by wealth groups across time. In order to measure inequity in the use of modern contraceptives, the study uses multivariate methods to control for differences in the need for family planning services in relation to household wealth. Results The results suggest that the expansion of the private commercial sector supply of contraceptives in the four study countries did not lead to increased inequity in the use of modern contraceptives. In Nigeria and Uganda, inequity actually decreased over time; while in Bangladesh and Indonesia, inequity fluctuated. Conclusions The study results do not offer support to the hypothesis that the increased role of the private commercial sector in the supply of contraceptive supplies led to increased inequity in modern contraceptive use.